In vitro pharmacological characterization of a novel unbiased NOP receptor‐selective nonpeptide agonist AT‐403. Issue 4 (25th July 2017) - Ferrari, Federica; Malfacini, Davide; Journigan, Blair V.; Bird, Mark F.; Trapella, Claudio; Guerrini, Remo; Lambert, David G.; Calo', Girolamo; Zaveri, Nurulain T.
Abstract: Nociceptin/orphanin FQ (N/OFQ) regulates several biological functions via selective activation of the N/OFQ receptor (NOP), a member of the opioid receptor family. We recently identified a new high affinity and highly selective NOP agonist AT‐403. In this study, we characterized the functional profile of AT‐403 and compared it to other known nonpeptide NOP agonists Ro 65‐6570, Ro 2q, SCH‐221510, MCOPPB, AT‐202 and SCH‐486757, using the following assays: GTP γ [ 35 S] stimulated binding, calcium mobilization assay in cells‐expressing human NOP or classical opioid receptors and chimeric G proteins, bioluminescence resonance energy transfer (BRET) based assay for studying NOP receptor interaction with G protein and arrestin, and the electrically stimulated mouse vas deferens bioassay. All compounds behaved as NOP full agonists consistently showing the following rank order of potency MCOPPB > AT‐403 > Ro 65‐6570 = Ro 2q > SCH‐221510 >  AT‐202 > SCH‐486757. AT‐403 and MCOPPB displayed the highest NOP selectivity both at human and murine receptors. Interestingly, while all the other nonpeptide NOP agonists displayed bias toward G protein‐mediated signaling in the BRET assay, AT‐403, similar to the natural ligand N/OFQ, behaved as an unbiased agonist, activating G‐protein‐mediated function as well as arrestin recruitment. AT‐403 may be a useful nonpeptide tool compound to study the pharmacology of NOP activation in disease states.